The Global Prevalence of Non-suicidal Self-injury, Suicide Behaviors, and Associated Risk Factors Among Runaway and Homeless Youth: A Meta-analysis - Armoon, Bahram; Mohammadi, Rasool; Griffiths, Mark D. (Community mental health journal, 2024)
A meta-analysis was performed to determine pooled prevalence of non-suicidal self-injury (NSSI), suicide behaviors (including ideation, attempts), and associated risk factors among runaway and homeless youth (RHY). The databases PubMed, Scopus, Web of Science, and Cochrane Library were searched for relevant studies published from January 1995 to May 2023. Initially, 8465 papers were screened, resulting in 69 included studies. The results showed that among RHY, lifetime prevalence rates were 42% for NSSI, 38% for suicidal ideation, and 27% for suicide attempts. Lifetime prevalence of NSSI and suicide behaviors was higher among adolescent minors (aged 12–17 years) compared to young adults (aged 18–24 years). Also, NSSI and suicide behaviors were associated with having a childhood history of physical and sexual abuse. Developing an impactful community-based suicide prevention campaign tailored for RHY appears warranted. Peer groups and mentorship programs would provide invaluable support for young individuals, as supportive friendships protect against NSSI.